Cost-effectiveness of nonavalent HPV vaccination in the Netherlands - Cody Palmer; Christiaan Dolk; Ugne Sabale; Wei Wang; Kunal Saxena (Taylor & Francis Group, 2024)
ABSTRACTBackground A bivalent human papillomavirus vaccine (2vHPV) is currently used in the Netherlands; a nonavalent vaccine (9vHPV) is also licensed.Research design and methods We compared the public health and economic benefits of 2vHPV- and 9vHPV-based vaccination strategies in the Netherlands over 100 years using a validated deterministic dynamic transmission metapopulation model.Results Compared to 2vHPV, the 9vHPV strategy averted an additional 3,245 cases of and 825 deaths from 9vHPV-strain-attributable cancers, 4,247 cases of and 190 deaths from recurrent respiratory papillomatosis (RRP), and 1,009,637 cases of anogenital warts (AGWs), with an incremental cost-effectiveness ratio (ICER) of €4,975 per quality-adjusted life year (QALY) gained. The ICER increased in a scenario with increased HPV vaccination coverage rates and was relatively robust to one-way deterministic sensitivity analyses, with variation in the disease utility parameter having the most impact. When catch-up vaccination for individuals ≤26 years of age was added to the model, vaccinating with 9vHPV averted additional cancers and AGWs compared to 2vHPV vaccination.Conclusion Our analyses predict that transitioning from a 2vHPV- to a 9vHPV-based vaccination strategy would be cost-effective in the Netherlands.